A Novel Grip-Type Microsurgical Needle Holder: Introduction and Electromyographic Evaluation - Yasunaga, Yoshichika; Yanagisawa, Daisuke; Ohata, Erika; Yuzuriha, Shunsuke; Kondoh, Shoji; Matsuo, Kiyoshi (Journal of Reconstructive Microsurgery Open, 2020)
Background We have newly developed a novel “grip-type” gun-shaped microsurgical needle holder that requires only finger twisting between the thumb and index finger for needle advancement. This study aimed to objectively assess whether this grip-type needle holder could reduce forearm muscle movement during microsurgical suturing as compared with a conventional pen-type needle holder by means of surface electromyography (sEMG).Methods Extensor carpi ulnaris (ECU) muscle and flexor carpi ulnaris muscle (FCU) sEMG measurements were taken during needle advancement in a microvascular anastomosis model for calculation of root mean square (RMS) values. The summed ECU and FCU RMS values were employed as indicators of forearm muscle movement and compared between the pen-type and grip-type instruments. Analyses of eight subjects and suturing in five directions by one subject were conducted.Results The summed ECU and FCU RMS values of the grip-type holder were significantly smaller than those of the pen-type holder in comparisons of eight subjects (p < 0.05). Similarly, the summed RMS values of the grip-type holder in each of the five suturing directions were remarkably lower than those of the pen-type holder.Conclusion The grip-type needle holder could significantly reduce forearm muscle movement as compared with a conventional pen-type holder based on objective sEMG measurements. The grip-type device appears more ideally suited for delicate microsurgical suturing, such as lymphaticovenular anastomosis or finger replantation, since the reduced forearm movement may mitigate the risk of coarse motion and hand shaking.
Keywords: needle holder; microsurgery; electromyography